A Requirements Index for Information Processing in Hospitals - Ammenwerth, E.; Buchauer, A.; Haux, R. (Methods of Information in Medicine, 2002)
Objectives: Reference models describing typical information processing requirements in hospitals do not currently exist. This leads to high hospital information system (HIS) management expenses, for example, during tender processes for the acquisition of software application programs. Our aim was, therefore, to develop a comprehensive, lasting, technology-independent, and sufficiently detailed index of requirements for information processing in hospitals in order to reduce respective expenses.Methods: Two-dozen German experts established an index of requirements for information processing in university hospitals. This was done in a consensus-based, top-down, cyclic manner. Each functional requirement was derived from information processing functions and sub-functions of a hospital.Results: The result is the first official German version of a requirements index, containing 233 functional requirements and 102 function-independent requirements, focusing on German needs. The functional requirements are structured according to the primary care process from admission to discharge and supplemented by requirements for handling patient records, work organization and resource planning, hospital management, research and education. Both the German version and its English translation are available in the Internet.Conclusions: The index of requirements contains general information processing requirements in hospitals which are formulated independent of information processing tools, or of HIS architectures. It aims at supporting HIS management, especially HIS strategic planning, HIS evaluation, and tender processes. The index can be regarded as a draft, which must, however, be refined according to the specific aims of a particular project. Although focused on German needs, we expect that it can also be useful in other countries. The high amount of interest shown for the index supports its usefulness.
Keywords: Hospital information system; information management; delivery of health care; needs assessment; quality assurance; process assessment (health care)